ANALISA PENYEBAB KETERLAMBATAN INPUT KODEFIKASI INDEKS PENYAKIT PASIEN RAWAT JALAN DI RUMAH SAKIT BETHESDA YOGYAKARTA - , R.A BUNGA APRILYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Background of Problem: The hospital is a health care facility for all the community, the main purpose of the hospital is to produce a favorable outcome, the outcome obtained depends on the quality of services provided. To take the necessary decisions with accurate information and timely to be a report. Indexing activity is one activity of a series of activities if the data reporting, ie the index is a list of important words or terms that have the same keywords, the indexing activities at the hospital include the index patient, disease index, and the index physician. In the disease index performed using manual coding of ICD-10. Based on the results of the study are documentation-recapitulation recapitulation daily census outpatients who have not been in the code and input into computer for indexing activities and materials reporting morbidity outpatient basis. The Aim of Research: To know the process of implementing the index coding of outpatient illness include charging diagnosis, inputting code outpatient disease, treatment and study data. To determine the factors causing delays in inputting coding of outpatient illness index at Bethesda Hospital and determine the impact of the delay in inputting coding of outpatient illness index at Bethesda Hospital. The Methodology of Research : Type of research used is descriptive research with a qualitative approach to data collection in the study of documentation, interviews, and observations. The study design is case study research. For the validation data using triangulation sumber.penentuan subject and object using purposive sampling. This research was conducted at Bethesda Hospital Yogyakarta. The Result of Research: Based on interviews, the process of filling the diagnosis on the medical record file is done by physicians who care for patients, charging diagnostics on the computer for recapitulation daily census is an outpatient clinic nurse. Inputting a code of disease carried by medical records personnel morbidity outpatient coding part. processing and presentation of data processing that include: coding, indexing, and then processed into outpatient morbidity report, presenting data that has been processed by the results of the interview are reported net patient morbidity (RL4B). Based on interviews the causes of the lack of human resources in terms of man to the census section, in terms of machines already support, there are constraints in terms of material but can be addressed independently by a clinical nurse, method discrepancy between the written standard operating procedures at Bethesda Hospital with officers in the field conditions . Based on interviews the impact of input delay codefication disease index was RL4B delayed delivery report (a report of outpatient morbidity) and incompleteness of data RL4B (outpatient morbidity reports)